Anti-inflammatory activity of a thermophilic serine protease inhibitor from extremophile Pyrobaculum neutrophilum. (December 2017) - Fei, Rui; Zhang, Huan; Zhong, Sheng; Xue, Baigong; Gao, Yuanqi; Zhou, Xiaoli
Serine protease inhibitors (serpins) are a superfamily of proteins involved in many important biological processes, including inflammation. Serpins dysfunction-related diseases are mainly treated by augmentation therapy using serpins purified from human plasma. Pnserpin from hyperthermophilic archaeon Pyrobaculum neutrophilum showed protease inhibition activity and high stability. In this study, we examined the anti-inflammatory activity of Pnserpin using xylene-induced acute inflammatory model of mouse ear swelling and lipopolysaccharide (LPS)-induced murine RAW 264.7 macrophages cellular model. The inhibition of mouse ear swelling and the production of pro-inflammatory cytokines in mouse serum or in macrophages cell were used to evaluate the anti-inflammatory effect of Pnserpin. Our results showed that Pnserpin could inhibit the xylene-induced mouse ear swelling and suppress the production of pro-inflammatory cytokines in mouse serum and in LPS-induced RAW264.7 cells. This study indicated that Pnserpin might have anti-inflammatory effect in vivo and in vitro.